Large effective population size masks population genetic structure in Hirondellea amphipods within the deepest marine ecosystem, the Mariana Trench. Issue 9 (3rd March 2023) - Piertney, Stuart B.; Wenzel, Marius; Jamieson, Alan J.
Abstract: The examination of genetic structure in the deep‐ocean hadal zone has focused on divergence between tectonic trenches to understand how environment and geography may drive species divergence and promote endemism. There has been little attempt to examine localized genetic structure within trenches, partly because of logistical challenges associated with sampling at an appropriate scale, and the large effective population sizes of species that can be sampled adequately may mask underlying genetic structure. Here we examine genetic structure in the superabundant amphipod Hirondellea gigas in the Mariana Trench at depths of 8126–10, 545 m. RAD sequencing was used to identify 3182 loci containing 43, 408 single nucleotide polymorphisms (SNPs) across individuals after stringent pruning of loci to prevent paralogous multicopy genomic regions being erroneously merged. Principal components analysis of SNP genotypes resolved no genetic structure between sampling locations, consistent with a signature of panmixia. However, discriminant analysis of principal components identified divergence between all sites driven by 301 outlier SNPs in 169 loci and significantly associated with latitude and depth. Functional annotation of loci identified differences between singleton loci used in analysis and paralogous loci pruned from the data set and also between outlier and nonoutlier loci, all consistent with hypotheses explaining the role of transposable elements driving genome dynamics. This study challenges the traditional perspective that highly abundant amphipods within a trench form a single panmictic population. We discuss the findings in relation to eco‐evolutionary and ontogenetic processes operating in the deep sea, and highlight key challenges associated with population genetic analysis in nonmodel systems with inherent large effective population sizes and genomes.